Design and development of a low‐cost biphasic charge‐balanced functional electric stimulator and its clinical validation. Issue 5 (21st October 2015) - Shendkar, Chandrashekhar; Lenka, Prasanna K.; Biswas, Abhishek; Kumar, Ratnesh; Mahadevappa, Manjunatha
Abstract : Functional electric stimulators that produce near‐ideal, charge‐balanced biphasic stimulation waveforms with interphase delay are considered safer and more efficacious than conventional stimulators. An indigenously designed, low‐cost, portable FES device named InStim is developed. It features a charge‐balanced biphasic single channel. The authors present the complete design, mathematical analysis of the circuit and the clinical evaluation of the device. The developed circuit was tested on stroke patients affected by foot drop problems. It was tested both under laboratory conditions and in clinical settings. The key building blocks of this circuit are low dropout regulators, a DC–DC voltage booster and a single high‐power current source OP‐Amp with current‐limiting capabilities. This allows the device to deliver high‐voltage, constant current, biphasic pulses without the use of a bulky step‐up transformer. The advantages of the proposed design over the currently existing devices include improved safety features (zero DC current, current‐limiting mechanism and safe pulses), waveform morphology that causes less muscle fatigue, cost‐effectiveness and compact power‐efficient circuit design with minimal components. The device is also capable of producing appropriate ankle dorsiflexion in patients having foot drop problems of various Medical Research Council scale grades.